Environmental Conditions and COVID-19 Incident - Yura Witsqa Firmansyah; Mirza Fathan Fuadi; Farida Sugiester S; Wahyu Widyantoro; Muhammad Fadli Ramadhansyah (Journal of Health Science and Prevention, 2021)
COVID-19 is a new infectious disease caused by the SARS-CoV-2 virus and was designated as a pandemic since March 12, 2020, because there are a lot of case in several countries. On February 1, 2021, the total number of COVID-19 cases reached 103 million in the world, and in Indonesia it reached 1.09 million. Many factors influence the transmission and death of COVID-19, for example environmental conditions. This study aims to provide an overview of environmental conditions that can be a factor for transmission and death due to COVID-19. The method in this research is literature review, which is a literature review with secondary data obtained through research journals which are then synthesized and obtained 23 articles as a reference for preparing literature reviews. COVID-19 and environmental degradation have decreased air, water, noise and marine pollution due to the lockdown, but there has been an increase in the volume of hazardous and toxic waste from COVID-19 patients. Then from air pollution, the results of decreases in CO, NO2, and PM10 during lockdown. Meanwhile, for climatology and meteorology, the result is that every 1oC increase in temperature from the average temperature can reduce daily cases of COVID-19 by 36% and 57% when the average humidity is at 67% and 85.5%. Likewis,e humidity each 1oC increase relatively reduces daily cases of COVID-19 by 11% to 22% with a temperature range of 5.04oC to 8.2oC. The conclusion of this research is that the environmental conditions during a pandemic had their own polemic. However, several pollutants such as CO, NO2, O3, PM2,5, and PM10 is closely related to the spread of COVID-19. This literature review can provide recommendations for an overall global government demonstration policy in the prevention and control of environmental pollution and recycling of medical waste.